Customer perceptions towards innovation products in the sphere of privacy versus security debate (the case of transmission x-ray body scanners in the UK) - Zelenkevich, Marina; Zelenkevich, Leonid (Management and Administration Journal, 2025)
This article attempts to establish potential applications for widening the use of transmission x-ray full body scanners in the United Kingdom (UK) as the product of innovation. It is the first research project of its kind and findings will be able to assist government agencies in enhancing current security systems within the transport and prison sectors of the UK. In addition, product manufacturers will be able to adjust their marketing and product development strategies. The main findings of this study demonstrated that introducing the product within the UK air transport and prison sectors could enhance individual privacy. The product would also be able to combat the issue of contraband trafficking within the air transport and prison sectors of the UK to enhance security. It was, however, highlighted that the product would not significantly improve staff and inmate safety within the prison sector. The issue of data security was also discussed and frequent travelers did not view the data produced by the product as being damaging to individual privacy, whilst a prison security manager viewed data security as one of the most significant issues associated with widening the use of the equipment. The results also demonstrated that transmission x-ray full body scanners are not suitable to be used within the UK rail network as the equipment would cause major inconveniences for train passengers. The next section of this article will focus on discussing introduction of the innovation product in the sphere of the debate of privacy vs. security.